Cruel utopia of the seas? Multiple risks challenge the singular hydrogen hype in Finnish maritime logistics - Janasik, Nina; Luoma, Emilia; Knudsen, Mikkel; Nikkanen, Maija; Hukkinen, Janne I. (Elsevier, 2026)
To address the global climate crisis, maritime logistics are undergoing a transition away from fossil-based energy sources. The transition is envisaged to be both green (involving renewables) and digital (involving various kinds of digitalization). Much of the hope rests on the new hydrogen economy, involving the build-up of infrastructure for hydrogen-derived alternative fuels such as methanol and ammonia. Indeed, the new hydrogen economy is often portrayed as set to revolutionize maritime transport. The hope behind the hype reflects a belief in the performativity of hypes: some technological phenomenon will eventually materialise in innovation and business practices. In this paper, we critically analyse the current hydrogen hype in the field of Finnish maritime logistics as a paradigmatic case of performative techno-optimism. Based on causal network analysis and thematic analysis of expert interviews and workshop data, we argue that the phenomenon of performative techno-optimism is more nuanced than hitherto presented in the related literature. We showcase a variety of stances along a spectrum ranging from radical optimism to radical pessimism. Furthermore, our causal network analysis indicates that the current green and digital transition of maritime transport is caught in a systemic catch-22: transitioning to alternative fuels in maritime logistics faces a lock-in of between overly cautious demand for alternative fuels leading to overly cautious investment in supply, which only secures the modest demand. Finally, our thematic analysis of techno-optimist stances suggests the following two major ways out of the systemic dilemma: large-scale technological innovations and global regulatory solutions.